Calretinin Interneurons are Early Targets of Extracellular Amyloid-beta Pathology in PS1/AbetaPP Alzheimer Mice Hippocampus. - Baglietto-Vargas, David; Moreno-González, Inés; Sánchez-Varo, Raquel María; Jiménez, Sebastián; Trujillo-Estrada, Laura Isabel; Sánchez-Mejías, Elisabeth; Torres, Manuel; Romero-Acebal, Manuel; Ruano, Diego; Vizuete, Marisa; Vitorica Ferrández, Javier; Gutiérrez-Pérez, Antonia; et al. (IOS Press, 2010)
Specific neuronal networks are preferentially affected in the early stages of Alzheimer’s disease (AD). The distinct subpopulations of hippocampal inhibitory GABAergic system have been shown to display differential vulnerability to neurodegeneration in AD. We have previously reported a substantial loss of SOM/NPY interneurons, whereas those expressing parvalbumin were unaltered, in the hippocampus of 6 month-old PS1/AβPP transgenic mice. In the present study, we now investigated the pathological changes of hippocampal calretinin (CR) interneurons in this PS1/AβPP model from 2 to 12 months of age. The total number of CR-immunoreactive inhibitory cells was determined by stereology in CA1 and CA2/3 subfields. Our findings show a substantial decrease (35%–45%) of CR-positive interneurons in both hippocampal subfields of PS1/AβPP mice at very early age (4 months) compared to age-matched control mice. This decrease was accompanied by a reduced CR mRNA content as determined by quantitative RT-PCR. However, the number of another hippocampal CR-positive population (belonging to Cajal-Retzius cells) was not affected. The selective early loss of CR-interneurons was parallel to the appearance of extracellular Aβ deposits, preferentially in CR-axonal fields, and the formation of dystrophic neurites. This specific GABAergic subpopulation plays a crucial role in the generation of synchronous rhythmic activity in hippocampus by controlling other interneurons. Therefore, early alterations of hippocampal inhibitory functionality in AD, caused by select CR-cells neurodegeneration, could result in cognitive impairments seen in initial stages of the disease.
Keywords: Alzheimer, Enfermedad de; Amiloide; Hipocampo (Cerebro); Sistema nervioso - Enfermedades; Neuronas; Sistema nervioso - Degeneración; Alzheimer's disease; Amyloid; Hippocampal formation; Neuropathology; Transgenic; Inhibitory neurons; Neurodegeneration